Reforming an Institutional Culture of Corruption: A Model of Motivated Agents and Collective Reputation - Justin Mattias Valasek (Center for Economic Studies and ifo Institute (CESifo), 2015)
Recent research has highlighted social image and identity concerns as factors that influence economic decisions. Given that an individual's choice of employment may be important for their social image, we consider a model of worker sorting into the mission-oriented or private sector with motivated agents who also value the collective reputation of their place of employment. The initial insight of the analysis is that, from the institution's perspective, there may exist both a high-reputation, low-wage equilibrium and a low-reputation, high-wage equilibrium, which raises the question of how an institution can transition between equilibria. Our main contribution is to characterize a dynamic wage path that will transition from a low-reputation to a high-reputation steady state: Importantly, the effect of wages on motivation depend on the initial reputation - starting from low-reputation, higher wages crowd in motivation, while starting from high-reputation, higher wages crowd out motivation. Therefore, a non-monotonic wage path is required to achieve a transition to the low-wage, high-reputation equilibrium - an initial wage increase to crowd in motivated workers, followed by a wage decrease to crowd out non-motivated workers. These results provide a novel explanation for empirical findings in developing nations that - in direct contrast to evidence from developed nations - public sector workers are less prosocial and higher wages weakly increase motivation. Lastly, we discuss the implication of our results for policy measures aimed at reforming an institutional culture of corruption.
Keywords: D23; D73; L32; 330; motivated workers; institutional reform; public sector